Evidance Based Pracrice Muskuloskeletal Dengan Rheumathoid - Manengkey, Olvin; Surapati, Venesia (Yayasan Syalom Cipta Sumikolah, 2025)
Rheumatoid Arthritis is a musculoskeletal disease that often occurs in old age and disrupts the musculoskeletal system, characterized by the appearance of joint pain and stiffness, resulting in a decrease in physiological abilities or quality of life. Pain management can be done with pharmacological or non-pharmacological therapy. This writing aims to discuss the nursing care provided to Mrs. S.L at Ranomuut nursing home. The intervention given to treat the main complaint of chronic pain is pharmacological drug administration and non-pharmacological administration, namely warm red ginger compress therapy and cutaneous stimulation. After the intervention, there was a decrease in the pain scale, namely from 7 to 5 after 5 hours of nursing action. The conclusion in this study is that intervention to treat pain can be carried out using pharmacological and non-pharmacological therapy. Researchers suggest that health workers and patients who experience pain due to rheumatoid arthritis can use non-pharmacological therapy.